2019
DOI: 10.1002/bit.27218
|View full text |Cite
|
Sign up to set email alerts
|

Gelatin interpenetration in poly N‐isopropylacrylamide network reduces the compressive modulus of the scaffold: A property employed to mimic hepatic matrix stiffness

Abstract: The progression of liver disease from normal to cirrhotic state is characterized by modulation of the stiffness of the extracellular matrix (ECM). Mimicking this modulation in vitro scaffold could provide a better insight into hepatic cell behavior. In this study, interpenetrating poly(N‐isopropylacrylamide‐co‐gelatin) cryogels were synthesized in 48 different compositions to yield scaffolds of different properties. It was observed that a high concentration of N‐isopropylacrylamide (NIPAAm) leads to the format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…More importantly, 5% GelMA, once solidified within DLM, provides biologically relevant stiffness and biomechanical properties resembled to native liver ECM in vivo 33,34 . Studies have shown that the stiffness in ECM can promote stem cell differentiation 35 , maintain cell functionality 36 , and reverse aged oligodendrocyte progenitor cells 37 . With this physiologically relevant stiffness and mechanical support, hepatocytes can be well immobilized within DLM with good cell viability (more than 90%), cell engraftment and cell…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, 5% GelMA, once solidified within DLM, provides biologically relevant stiffness and biomechanical properties resembled to native liver ECM in vivo 33,34 . Studies have shown that the stiffness in ECM can promote stem cell differentiation 35 , maintain cell functionality 36 , and reverse aged oligodendrocyte progenitor cells 37 . With this physiologically relevant stiffness and mechanical support, hepatocytes can be well immobilized within DLM with good cell viability (more than 90%), cell engraftment and cell…”
Section: Discussionmentioning
confidence: 99%
“…Some domain in collagen (like Phe-Hyp-Gly unit) can act as ligands for the integrin family receptors of cell surface, and potentially activate specific biological signals to promote cell attachment and proliferation. 43 In this work, HepG2 cells were used to detect the biological performance of the PVA/COL (0.8%) and PVA scaffolds. The SEM images intuitively displayed the growth and distribution of cells on the scaffolds.…”
Section: Discussionmentioning
confidence: 99%
“…8 For instance, poly(hydroxyethyl methacrylate) (PHEMA), poly(vinyl alcohol) (PVA), poly(ethylene glycol) (PEG), poly(ethylene glycol)-diacrylate (PEGDA), polycaprolactone (PCL), poly(acryl amide)/ poly(acrylic acid), gelatin methacryloyl (GelMA), poly(propylene fumarate) (PPF), poly(oligo ethylene glycol methacrylate) (POEGMA), and poly(N-isopropylacrylamide) (PNIPAM) are the typical synthesized materials that have been widely adopted to produce tissue-engineering hydrogels. 7,8,65,69,72,75,76,134,181 These synthetic materials are often modified macromers that present elongated degradation rates and make tissue engineering more tunable. 182,183 For example, thio-b ester-modified PEGDA hydrogels provide tunable degradation rates without changing the network of the PEGDA hydrogel.…”
Section: Synthetic Materialsmentioning
confidence: 99%